Impact of Information Technology in Indian Banking Industry: A Review - Kumar sadineni, Praveen; Agarwal , Dr. Sanjay (Innovative Research Thoughts, 2017)
Technological innovations witnessed by the banking sector during the nineties have changed the way business needs to be conducted. IT has introduced new business paradigms and is increasingly playing a significant role in improving the services in the ban king industry. There is a long history of banking services in India. The history of banking is as old as human history. More particularly in the area of Information Technology (IT), where India has definitely an edge over its competitors, remaining away or uniformity of the world trends is untenable. Financial sector in general and banking industry in particular is the largest spender and beneficiary from information technology. This endeavours to relate the international trends in it with the Indian banking industry